Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Bumi Sawit Kencana Wilmar - Erwin Dafis Nasution; Agatha Ayiek Sih Sayakti; Kadarwati Budihardjo (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
This research was conducted at PT. Bumi Sawit Kencana Wilmar located in Sei Sebabi Village District KM 82, Central Kalimantan, this company is engaged in processing oil palm. In this research, training and work motivation are independent variables and the dependent variable is employee performance. Sampling in this study using census sampling method, which is sampling technique where all members of the population are sampled, this is done because the population is relatively small. Based on this study there is how much influence of training and motivation on employee performance. The results of this study showed that training and motivation together have significant effect on employee performance where the value of F arithmetic (88.890)> F table (3.903), while the partial independent variable training has a positive effect on employee performance where t value (4,264) > t table (1,975), while independent variable of motivation have positive influence with t arithmetic (13,327) <t table (1,975). Results of Coefficient of Determination of Adjusted R Square value of 0.533. this illustrates that the employee's performance is able to be influenced by training and motivation of 53.33%.